Hypohydrotic ectodermal dysplasia: A rare case series - Manisha Goyal; Ashok Gupta; Priyanshu Mathur; Manish Sharma (Wolters Kluwer Medknow Publications, 2018)
Hypohydrotic ectodermal dysplasia (HED) is characterized by classical triad of Hypotrichosis (sparseness of scalp and body hair), anhidrosis/hypohidrosis (absence or reduction of sweat glands), and hypodontia/ anodontia (congenital absence of teeth). The sweating is greatly deficient, leading to episodes of hyperthermia. It is inherited as, X-linked form (caused by mutations in EDA gene), autosomal recessive and autosomal dominant form (caused by mutations in EDAR and EDARADD). We are describing three cases of HED and discussing their diagnostic and therapeutic approach.